Diabatic Rossby waves in the Southern Hemisphere. (13th September 2015) - Boettcher, Maxi; Wernli, Heini
Abstract : Diabatic Rossby waves (DRWs) are a special type of low‐level cyclone with a self‐maintaining mechanism given an environment of moderate or strong baroclinicity and abundant moisture. Under certain conditions, these shallow cyclones associated with a cyclonic low‐level PV anomaly can serve as precursors for explosive cyclone intensification. The present study is the first to investigate DRWs in the Southern Hemisphere (SH). Two typical DRW case‐studies are presented and a sophisticated algorithm is used to detect DRWs in operational analysis data from 2001 to 2012. DRWs occur in all ocean basins and seasons with a maximum in summer. On average, about four DRWs are found per month and 12% intensify explosively. Thereby, they contribute 6% to the total set of explosively deepening extratropical cyclones in the SH. DRW tracks originate slightly closer to the Equator than normal extratropical cyclones, and they follow the convergence zones eastward and poleward. This results in a climatological DRW track density similar to a spiral, from the western South Pacific ending in the eastern South Indian Ocean, broken only by the Andes. Typical synoptic situations associated with DRW genesis are identified. The categories include (i) low‐level PV generation by upper‐level induced lifting, (ii) low‐level jet‐induced diabatic PV generation, and (iii) transformation of the low‐tropospheric PV anomaly from another system.